Caracterización del poliestireno expandido (EPS) como adhesivo asfáltico empleando mezclas acetona-acetato de etilo - Quintero Castellanos, Heider Antonio (Universidad Antonio Nariño, 2022)
Currently, the inadequate management of urban solid waste generates environmental problems due to the incorrect handling and final disposal of the same, this environmental impact is caused mainly by the large volume required for its disposition in sanitary landfills. Within solid waste we find expanded polystyrene (Expanded PolyStyrene, EPS), which is a material that is not usually recycled because it is not provided with an adequate postprocessing that allows its reprocessing in new products, despite the fact that there are rocedures and technologies that allow its reuse through various recycling techniques, among which echanical recycling and chemical recycling stand out.